PERSAMAAN DAN PERBEDAAN SETSUZOKUSHI GA, KEDO DAN DEMO DALAM NOVEL FURU KARANGAN KANAKO NISHI - Titisari Puspa Indrati; Ni Wayan Meidariani; Wayan Nurita (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2021)
This research aims to determine and describe the similarities and the differences between ga, kedo and demo as setsuzokushi. This research is descriptive - qualitative. The data source of this research is a novel written by Kanako Nishi, titled Furu. The data are sentences in novel that containing ga, kedo and demo as setsuzokushi. Data were analysed using theory of setsuzokushi by Chino and Tanimori. Result of this research are ga, kedo and demo are used to combining two sentences or two clauses which have opposite meaning. The differences are ga in this novel is used only for written language, kedo only for spoken language, and democan be used for both written dan spoken language. By the position in sentence, ga can be used in front or the middle of sentences, kedo in middle or end of sentence and demo can be used in front or middle of sentence.